2018
DOI: 10.3892/etm.2018.6888
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑466 inhibits osteosarcoma cell proliferation and induces apoptosis by targeting CCND1

Abstract: Emerging pieces of evidence indicate that microRNA-466 (miR-466) serves as a tumor suppressor in several human tumors, including colorectal cancer and prostate cancer. However, whether miR-466 is involved in osteosarcoma (OS) progression remains largely unknown. The present study demonstrated that miR-466 was significantly downregulated in OS tissues and cell lines. Furthermore, it was revealed that the expression of miR-466 was negatively correlated with OS severity. Moreover, low miR-466 expression in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…miR-466 has been shown to be a tumor suppressor in osteosarcoma ( 31 ) and colorectal cancer ( 32 ). miR-466 regulates its target gene RUNX2 to inhibit bone metastasis and tumor growth in prostate cancer ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…miR-466 has been shown to be a tumor suppressor in osteosarcoma ( 31 ) and colorectal cancer ( 32 ). miR-466 regulates its target gene RUNX2 to inhibit bone metastasis and tumor growth in prostate cancer ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed all the proliferation-related genes appeared to be up-regulated after the CYP19A1 knockdown. Previous studies have demonstrated that all of them play important regulatory roles in cell proliferation and the cell cycle (21)(22)(23)(24). For example (25), found that neuron growth factors (NGF) promote the proliferation of granulosa cells (GC) by downregulating ESR2 and CDKN1A.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we found that miR‐466 was abundantly bound by PGM5‐AS1, as demonstrated by RNA pull‐down and luciferase reporter assays. miR‐466 was reported as a tumor suppressor in osteosarcoma, colorectal cancer, and prostate cancer, while as an oncogene in cervical cancer, implying that miR‐466 is expressed in a disease‐or tissue‐specific manner. However, its role in ESCC remains unknown.…”
Section: Discussionmentioning
confidence: 99%